Determinasi Luxury Brand terhadap Purchase Intention pada Generasi Y - Elistia, Elistia; Lorenza, Gita (Jurnal Ekonomi : Journal of Economic, 2023)
Market growth and purchases of luxury brand products are growing marked by increased purchase intention; this is an exciting research topic to study, especially in Indonesia, because there is not much research on the topic of Determinants of luxury brand purchase intention in Generation Y. Thus, further studies need to conduct what factors influence the purchase intention of luxury brands. The determinants of the proposed purchase intention are perceived value, brand equity, consumption status, and social media marketing. This research uses descriptive causality with a quantitative method approach. The population in this study is Generation Y consumers who live in the Jakarta area, and the sampling technique was purposive sampling with a total sample of 230 respondents. The data was processed and analyzed using SEM-PLS 4. The results of this study indicate that Perceived Value, Brand Equity, and Social Media Marketing positively affect Purchase Intention. However, conversely, Status Consumption has no significant effect on Purchase Intention. Furthermore, it moderates negatively for Consumer Vanity, meaning it weakens the relationship between Perceived Value and Purchase Intention. Thus, Perceived Value, Brand Equity, and Social Media Marketing can increase Purchase Intention. This research helps provide insight to consumers on the factors in buying luxury brand products. As well as luxury brand companies can make strategies on how to develop their products and brands based on which factors are more supportive of purchase intention.